Body Mass Index, Physical Activity, High Normal Fasting Plasma Glucose levels and the risk of Diabetes Mellitus Type 2 - Nasreen Qazi, Madiha Shah, Shaheen Shah, Manzoor Unar, Gulshan Ara Jalbani, Mahboob Ahmed Wagan (Journal of Rawalpindi Medical College, 2010)
Background: To find out the relationship between obesity, sedentary lifestyle and fasting plasma glucose (FPG)levels in apparently healthy individuals belonging to the paramedical staff of the Liaqat University of Medical and Health Sciences, Jamshoro. Methods: 50 healthy individuals were included in the study. FPG levels were measured at baseline and after three years. Body mass index was calculated as weight in kilograms divided by the square of the height in meters, and the subjects were defined as obese if their BMI was 30 or greater. A specially designed questionnaire NICE guideline- PHI2 Physical activity: Implementation advice 2006 was filled at baseline & at the end of the study. Patients with known DM were excluded from the study. Results: At baseline the mean FPG level was 88 ± 5.62 mg/dl which increased to 98.4 ± 4.22 mg/dl in a three year period. 41% of subjects had FPG of ≥100 when followed up after 3 years. There were two incident cases of DM Type 2. The study revealed that in men with FPG of 100 mg/dL or higher there was a progressively greater risk for type 2 diabetes as the FPG values rose, compared with men who had an FPG of less than 86 mg/dL, p <0.001. A similar large risk was detected in men with a BMI of 30 or more, compared with a BMI less than 25 .It was also observed that most of the subjects were among the moderately inactive group. Conclusion: Persons with normal blood sugar at a given examination, who are over weight and living a sedentary life style; can develop diabetes in coming years as compared to people with less BMI and lower normal fasting plasma glucose levels.